2020
DOI: 10.21037/apm-20-1078
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 regulates CX3CL1/CX3CR1 in the early phase of neuropathic pain in chronic sciatic nerve constriction injury (CCI) rats

Abstract: Background: To observe the effects of MMP-9 (matrix metalloproteases-9) on the mechanical allodynia and thermal hyperalgesia and the expression of CX3CL1 (CX3C chemokine ligand 1) protein in the spinal dorsal root ganglion (DRG) in rats with chronic sciatic nerve constriction injury (CCI).Methods: A total of 84 male SD rats were randomly divided into seven groups, namely the normal group , the sham operation group , the model group , the CCI + MMP-9 group, the CCI + TIMP-1 group , the CCI + siRNA group, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The fractalkine receptor, CX3CR1, a marker of peripheral monocytic cells and microglia, was increased in the ipsilateral DRG in a spared nerve injury-induced neuropathic pain model [ 67 ]. In addition, the involvement of MMP-9 in the early phase of neuropathic pain in CCI rats was related to the upregulation of C-X3-C Motif Chemokine Ligand 1 (CX3CL1)/CX3CR1 [ 68 ]. Our results showed that CJE, (−)-epicatechin, and rutin treatment significantly reduced the upregulation of gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…The fractalkine receptor, CX3CR1, a marker of peripheral monocytic cells and microglia, was increased in the ipsilateral DRG in a spared nerve injury-induced neuropathic pain model [ 67 ]. In addition, the involvement of MMP-9 in the early phase of neuropathic pain in CCI rats was related to the upregulation of C-X3-C Motif Chemokine Ligand 1 (CX3CL1)/CX3CR1 [ 68 ]. Our results showed that CJE, (−)-epicatechin, and rutin treatment significantly reduced the upregulation of gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 is significantly associated with the onset of neuropathic pain rather than its maintenance (28). However, specific molecular mechanisms related to MMP9 and DRG inflammation pain are lacking; this mechanism should be further investigated, as MMP9 may be a novel candidate biomarker for DRG inflammation pain.…”
Section: Discussionmentioning
confidence: 99%
“…During nervous system development and following injury, MMPs have been increasingly recognized as playing vital roles [24]. For example, MMP-9 was associated with the early process of neuropathic pain in CCI rats [25]; and in peripheral nerve regeneration, MMP-7 promoted myelin sheath formation and Schwann cell migration [15]. As the smallest member of MMPs, MMP-7 plays vital roles in many physiological processes [26].…”
Section: Discussionmentioning
confidence: 99%